Análisis bibliométrico sobre trabajo y salud laboral en trabajadores informales, 2010-2016 - Katherin Johana Puentes-León; Lyda Yolima Rincón-Bayona; Alexandra Puentes-Suárez (Universidad de Antioquia, 2018)
Objective: To analyze the scientific work published between 2010 and 2016 in free and restricted access databases on work and occupational health of informal workers. Methodology: We reviewed the scientific literature on work and occupational health of informal workers, published in free and restricted access databases. This descriptive study was developed from bibliometric indicators: content, author affiliation, methodological and productivity. Results: 71 units of analysis were obtained, which met the established inclusion criteria. 32% of the articles addressed issues related to working conditions and health; economic activity varies for different sectors and activities catalogued as informal - street vendors and waste collectors stood out. The studies analyzed identified different risks and their impact on health associated with working conditions. In terms of work characteristics, the lack of affiliation to the social security system, long working hours and the violation of rights were noted. The main reasons for entering the informal sector highlighted the impossibility of being employed in the formal sector. For the most part, the authors who contributed to this topic are transitory. Colombia contributed 45% of the total output on the subject and 2013 was the year with the greatest number of publications. Conclusions: Informal workers perceived advantages associated with time management, decision making and sharing time with the family; in terms of disadvantages, the precariousness of wages and the absence of health protection and pensions were mentioned.